Rat hippocampal responses up to 90 days after a single nanoceria dose extends a hierarchical oxidative stress model for nanoparticle toxicity. Issue 1 (August 2014) - Hardas, Sarita S.; Sultana, Rukhsana; Warrier, Govind; Dan, Mo; Wu, Peng; Grulke, Eric A.; Tseng, Michael T.; Unrine, Jason M.; Graham, Uschi M.; Yokel, Robert A.; Butterfield, D. Allan
Abstract Ceria engineered nanomaterials (ENMs) have very promising commercial and therapeutic applications. Few reports address the effects of nanoceria in intact mammals, let alone long term exposure. This knowledge is essential to understand potential therapeutic applications of nanoceria in relation to its hazard assessment. The current study elucidates oxidative stress responses in the rat hippocampus 1 and 20 h, and 1, 7, 30 and 90 days following a single systemic infusion of 30 nm nanoceria. The results are incorporated into a previously described hierarchical oxidative stress (HOS) model. During the 1–20 h period, increases of the GSSG: GSH ratio and cytoprotective phase-II antioxidants were observed. During the 1–7 d period, cytoprotective phase-II antioxidants activities were inhibited with concomitant elevation of protein carbonyl (PC), 3-nitrotyrosine (3NT), heme oxygenase-1 (HO-1), cytokine IL-1β and the autophagy marker LC-3AB. At 30 day post ceria infusion, oxidative stress had its major impact. Phase-II enzyme activities were inhibited; concurrently PC, 3NT, HO-1 and Hsp70 levels were elevated along with augmentation of IL-1β, pro-apoptotic pro-caspase-3 and LC-3AB levels. This progress of escalating oxidative stress was reversed at 90 days when phase-II enzyme levels and activities were restored to normal levels, PC and 3NT levels were reduced to baseline, cytokine and pro-caspase-3 levels were suppressed, and cellular redox balance was restored in the rat hippocampus. This study demonstrates that a single administration of nanoceria induced oxidative stress that escalates to 30 days then terminates, in spite of the previously reported continued presence of nanoceria in peripheral organs. These results for the first time confirm in vivo the HOS model of response to ENM previously posited based on in vitro studies and extends this prior hierarchical oxidative stress model that described three tiers to a 4th tier, characterized by resolution of the oxidative stress and return to normal conditions.